The Canadian Reinsurance Market in 2003 - Robey, Christopher; Fillmore, Keith (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2003)
Admittedly, the previous decade was not the best for the reinsurance industry. In this article, the authors provide an overview of the current reinsurance market conditions by reviewing the dramatic changes in the market which occurred since the late 1990's and then look at the current reinsurance situation both in Canada and globally. Here are the main themes discussed by the authors: Canada's Place in the Global Reinsurance Market, Impact of September 11, 2001 on the Reinsurance Market, 2002 Renewals, Current Reinsurance Market Conditions, Underlying Challenges and Major Risk Exposures, 2001 Global Catastrophes, Declining Investment Yields, and 2003 Renewals for Canadian Insurance Business.